The Correlation of Work Duration and Physical Workload with the Complaints of Musculoskeletal Disorders in Informal Workers - Nisrina Tiara Sani; Noeroel Widajati (Universitas Airlangga, 2021)
Introduction: The implementation of protection needs to be given attention and attempted to prevent workers from occupational diseases. One of the occupational diseases that often arises from the incompatibility of worker and their job is Musculoskeletal Disorders (MSDs). This study analyzes the relation between workduration and physical workload with MSDs in informal workers. Methods: An observational research followed by a cross sectional approach was applied as the method of the study. The 23 respondents in the spring production unit were chosen as the sample of the study. The objects of this research were the total population. Data on the characteristics of respondents and MSDs were gained through interviews conducted by filling out standardized questionnaires.Moreover, physical workload was measured using a calorimeter measuring instrument, and MSDs data were analyzed using the NBM measuring tools. Furtermore, the statistical analysis used chi-square test. Results: It shows that there is a relation between work duration and MSDs (p = 0.029), and there is a relation between physical workload and MSDs (p = 0.000). Conclusion: The risk factors of works duration and physical workload are proven to have a relation with MSDs complaints on workers in informal sector.Keywords: informal workers, musculoskeletal disorders, physical workload, works duration